Surgical resection of giant pleural solitary fibrous tumor: a case report - Alrefai, Mohammed A.; Mirza, Maryam; Alhumud, Abdullah A.; Almatrudi, Mazen; Alqahtany, Leen Y.; Alkurdi , Abdullah A. (International Journal of Research in Medical Sciences, 2024)
Solitary fibrous tumors of the pleura (SFTP) are uncommon neoplasms. We present the case of a 73-year-old male diagnosed with SFTP, exhibiting two masses measuring 20×18 cm and 9×8 cm in diameter, resulting in a notable cardio mediastinal shift towards the right side. The patient underwent successful surgical resection without experiencing any postoperative complications and was discharged in favorable condition. Although complete resection diminishes the risk of recurrence in both malignant and benign SFTP cases, long-term follow-up is necessary.